ANALISIS DIMENSI BANGUNAN RESAPAN AIR HUJAN UNTUK LAHAN PEKARANGAN - , Benedictus Deddy Setiadi, ST. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Global warming and lack of water are serious issues. The mindset of problem solving in urban drainage system, i.e. stormwater runoff has to be drained as soon as possible to the river or to the sea must be changed. Artificial infiltration is one of several way of ground water conservation that storm water runoff infiltrated by artificially as ground water recharge. Many formulas have been developed and being used such as Sunjoto (1988), SNI 03-2453- 2002, HMTL â ITB 1990, Association of Rainwater Storage and Infiltration Technology for Japanese (1995), Georgia Storm water Management Design, New York Storm water Management Design, California Storm water Management Design, Mohammad Rusli â UII 2008, Minnesota Urban Small Sites BMPM, Storm water Management Manual for Malaysia, Storm water Management Manual for Western Australia and Storm water Management Manual for Montgomary County Maryland. They analyzed by dimension analysis, parameter analysis and models testing to get equation which efficient and resemble with stream flow. The parameters that analyzed are storm water intensity, area of trench or well base and permeability coefficient. Each parameters analyzed with variation value starts from zero and continued with five value bigger. There are eight kind of models by unification of trench â well, impermeable wall â porous wall and have content material â empty. They tested by three experiments. The first experiment by using constant discharge (Qin) in 2 hours duration ( t ). The second experiment by using Qin1 in t1 = 30 minutes and t3 = 60 minutes and Qin2 in t2 = 30 minutes where Qin1 < Qin 2 and Qin2 = Qin at first experiment. The third experiment by using Qmaks = Qin2 in t = t1+ t2. The result of comparison analysis with same data show that Sunjotoâs formula give more logical value than others. In laboratory test, Sunjotoâs formula give the smallest Daverage (the average of the difference between Hdesign and Hactual in persen ) than others.